Quality Facetsof a UX LMS Affective Model for the Design and Evaluation of Learning Management Systems - et.al, Azham Hussain (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study looked into extant literature to elicit a mapping relationship for the affective component of Bloom’s learning taxonomy and a theoretical affective model for the design and evaluation of the affective experiences of users of and learners on learning management system (LMS) platforms. The study found that no prior affective model exists specifically for the design and evaluation of the affective experiences of LMS users. The study then mapped the affective component of the Bloom’s taxonomy of learning with the conceptual affective model and captured corresponding suitable quality facets/dimensions that influence and contribute to the model. This model is particularly appropriate for the design and evaluation of the affectivity of LMS platforms.